Study for the development an action programme for the linkage and convergence of different integration schemes : overview (ALADI MontevideoUY, 1994)
Posits the objective of creating a regional economic space which would have as its main components a free trade zone-type scheme for the trading of goods, a scheme for the liberalization of trade in services, economic cooperation programmes on sectors and issues of relevance to reciprocal relations, and a flexible mechanism for concerted action in economic relations with third countries and groups of countries.
DC